A welding method for solving the selective silver-plated surface of ceramic copper-clad substrate
By pickling, sandblasting and selective silver plating on the surface of the ceramic copper clad substrate, coating composite slurry on the non-patterned surface and performing high-temperature insulation, the problem of insufficient deformation and heat dissipation performance of the ceramic copper clad substrate during welding is solved, and good welding bonding, heat dissipation and strength are achieved.
Patent Information
- Application Number
- CN202410850957.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Ceramic copper clad substrates are prone to welding deformation, cracks or breaks during welding, and their heat dissipation performance is poor, making it difficult to meet the needs of high-power devices.
By pickling and sandblasting the surface of the copper clad substrate, the silver-plated copper-plated substrate is selected as the pattern surface and the other side is the non-patterned surface, and the silver-plated copper-plated substrate is obtained. Then sandblasting is performed on the non-pattern surface, composite slurry is coated, and organic solvents are removed through high temperature insulation, and finally the ceramic copper clad substrate is welded at high temperature.
It improves the welding bonding, heat dissipation and strength of ceramic copper clad substrates, and meets the application needs in electronic devices and aerospace fields.
Smart Images

Figure CN118870677B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-clad boards, in particular to a welding method for solving the problem of selective silver-plating on the surface of a ceramic copper-clad substrate. Background Art
[0002] Ceramic copper clad substrates have important value in modern times, mainly reflected in: Ceramic copper clad substrates are widely used in the field of electronic devices. With the rapid development of electronic technology, the performance requirements of electronic devices are getting higher and higher, and ceramic copper clad substrates, as a high-performance substrate material, can meet the various requirements of advanced electronic devices for substrate materials. For example, in the fields of high-frequency circuits, microwave devices, power devices, etc., ceramic copper clad substrates can provide stable and reliable basic support to ensure the normal operation of electronic devices.
[0003] Ceramic copper-clad substrates usually have complex structures and a combination of multiple materials. Therefore, parameters such as temperature, time and pressure need to be precisely controlled during the welding process to ensure the quality and stability of the welded joints. However, due to the large difference in the thermal expansion coefficients of ceramic and copper materials, welding deformation or cracks are easily caused during the welding process, thus affecting the welding quality. In addition, the welding process is also prone to bending, cracking or breaking of ceramic copper-clad substrates. In order to ensure the quality of welding, effective protective measures need to be taken during the welding process to reduce the occurrence of oxidation reactions, and new bonding materials or processes need to be developed to improve the interface bonding strength and durability. In addition, in terms of heat dissipation, the thermal conductivity of ceramic copper-clad substrates is relatively poor, and the heat dissipation effect is limited, which makes it difficult to meet the requirements of high-power devices for heat dissipation performance. High-density electronic devices generate a lot of heat when working. If the heat dissipation is poor, the device performance will be reduced or even damaged. In summary, there are many technical pain points in the welding process, strength and heat dissipation of ceramic copper-clad substrates. Continuous research and development and optimization are needed, especially in the improvement of welding process and the improvement of heat dissipation performance. Further efforts and explorations are needed to promote the wide application and development of ceramic copper-clad substrates in electronic devices and other fields.
[0004] In order to overcome the defects of the prior art, the present invention provides a method for welding the selective silver-plated surface of a ceramic copper-clad substrate. Summary of the invention
[0005] The object of the present invention is to provide a method for welding the selective silver-plated surface of a ceramic copper-clad substrate to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for welding a selective silver-plated surface of a ceramic copper-clad substrate, comprising the following steps:
[0008] Step 1: Take a copper-clad substrate, use one side of the copper-clad substrate as a pattern surface, and perform selective silver plating; use the other side as a non-pattern surface, and perform full silver plating to obtain a silver-plated copper-clad substrate;
[0009] Step 2: attach the solder sheet to the non-patterned surface of the silver-plated copper-clad substrate, sinter and dissolve it at high temperature, then place the chip, and finally prepare the ceramic copper-clad substrate through high-temperature soldering.
[0010] More optimally, in step 1, when the graphic surface of the copper-clad substrate is selectively silver-plated, the unnecessary area of the graphic surface is masked with ink, the area requiring silver plating is exposed for plating, and the non-graphic surface of the copper-clad substrate is fully silver-plated, and finally a silver-plated copper-clad substrate is obtained; wherein during the selective silver plating and the full silver plating, the plating solution includes 1.0-2.0 g / L silver ions, 5-30 g / L copper ion complexing agent, 0.5-2.0 g / L bithiazole compounds, 0.5-1.5 g / L nitrogen-containing indole compounds, 0.05-0.1 g / L benzotriazole, 40-60 ml / L methane sulfonic acid, 0.5-1.5 g / L polyphenylene tetracarboxamide; the silver plating pH is 0.5-1.0, the silver plating temperature is 50-60° C., the silver plating time is 2-5 min, and the silver plating thickness is 0.3-0.6 um.
[0011] More optimally, in step 1, the surface of the copper-clad substrate needs to be pickled and sandblasted before silver plating.
[0012] More optimally, the pickling process: immerse the copper-clad substrate in hydrochloric acid with a volume fraction of 2-20% for 15-20s; sandblasting: first prepare a corundum suspension with a concentration of 15-25wt%, and then spray the corundum suspension onto the surface of the copper-clad substrate, maintaining a pressure of 1.5-2.5kg / cm, a linear speed of 1.3-1.7m / min, and a tank temperature of 15-25°C. After sandblasting, keep the surface clean and ensure that the conductivity of the washing water is less than 2us / cm 3 .
[0013] More optimally, in step 2, before attaching the solder sheet to the non-patterned surface of the silver-plated copper-clad substrate, it is necessary to first perform sandblasting, apply composite slurry, and heat preservation at high temperature to remove the organic solvent.
[0014] More optimally, the preparation process of the composite slurry is as follows: a silver nitrate solution with a concentration of 0.6-0.7 g / L is heated to boiling, and then a sodium citrate solution with a concentration of 8-10 g / L is added to stir and react for 1-2 hours. After the reaction is completed, it is cooled to 25-30°C, and then a sodium citrate solution with a concentration of 400-500 g / L is added for flocculation. After the flocculation is completed, the nanosilver slurry is obtained by centrifugation and removal of the supernatant; the nanosilver slurry is mixed with propanol, and ultrasonic dispersion is performed to obtain solution 1; spherical silica, nano-graphene, nano-silicon carbide and propanol are mixed, and ultrasonic dispersion is performed to obtain solution 2; solution 1 and solution 2 are mixed evenly, and then acetone is added to mix evenly, and then centrifugation is performed and the supernatant is removed to obtain a composite slurry.
[0015] More optimally, the mass ratio of nanosilver slurry to propanol in solution 1 is 1:(3-3.5); the mass ratio of spherical silica, nanographene, nanosilicon carbide and propanol in solution 2 is (0.5-0.8):0.3:0.1:10; the mass content of nanosilver in the composite slurry is 96-98%.
[0016] More optimally, sandblasting treatment: first prepare a 15-25wt% corundum suspension, then spray the corundum suspension onto the non-graphic surface of the silver-plated copper-clad substrate, maintain a pressure of 1.5-2.5kg / cm, a linear speed of 1.3-1.7m / min, and a tank temperature of 15-25°C. After sandblasting, keep the surface clean and ensure that the conductivity of the washing water is less than 2us / cm 3 ; High temperature insulation parameters: 100-120℃ insulation for 2-4h.
[0017] More optimally, in step 2, the solder sheet is any one of Sn96.5Ag3.0Cu0.5 alloy, Sn95.2Ag4.0Cu0.8 alloy, and Sn97.2Ag2.5Cu0.3 alloy.
[0018] More optimally, in step 2, the high-temperature sintering dissolution parameters are: sintering temperature is 1065-1083°C, and sintering time is 1-2h; high-temperature welding parameters are: welding temperature is 200-300°C, and welding time is 50-80min.
[0019] Beneficial effects of the present invention:
[0020] The present invention firstly performs pickling and sandblasting on the surface of the copper-clad substrate, and then uses one side of the copper-clad substrate as a graphic surface for selective silver plating; and uses the other side as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate. Then, the non-graphic surface of the silver-plated copper-clad substrate is sandblasted, coated with composite slurry, and heat-insulated at high temperature to remove organic solvents. After the completion, a solder sheet is attached to the non-graphic surface of the silver-plated copper-clad substrate, sintered and dissolved at high temperature, and then a chip is placed, and high-temperature welding is performed to finally prepare a ceramic copper-clad substrate.
[0021] The present invention is characterized in that, in step 1, the surface of the copper-clad substrate is first pickled and sandblasted, and after the end, one side of the copper-clad substrate is used as a graphic surface for selective silver plating; the other side is used as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate. Impurities and oxide layers on the surface of the copper-clad substrate can be removed by pickling. The sandblasting of this step can make the copper surface rougher, improve the adhesion ability of the surface, and increase the contact area between the silver-plated layer and the copper surface, which is conducive to the adhesion and reliable connection of subsequent coatings. Through the silver plating treatment, a chemical silver plating liquid is used to plate a reduced silver layer on the metal surface, aiming to achieve the purpose of welding, rust prevention, wear resistance and enhanced conductivity of the product. Among them, the full silver-plated area is suitable for attaching chips with large areas, while the selective silver-plated area is suitable for attaching chips with small areas. Such a treatment can not only more effectively meet the mounting requirements of chips of different sizes, improve the flexibility and adaptability of the product, but also avoid unnecessary silver plating, thereby saving materials and production costs, making the silver plating process more accurate and economical.
[0022] The present invention is characterized in that, in step 2, the non-graphic surface of the silver-plated copper-clad substrate is sandblasted, coated with a composite slurry, and kept at high temperature to remove the organic solvent. After completion, a solder sheet is attached to the non-graphic surface of the silver-plated copper-clad substrate, sintered and dissolved at high temperature, and then a chip is placed, and high-temperature welding is performed to finally prepare a ceramic copper-clad substrate. In this step, the non-graphic surface of the silver-plated copper-clad substrate is sandblasted again. Through the sandblasting, on the one hand, the surface dirt and oxide impurities of the non-graphic surface can be removed to ensure the surface cleanliness; on the other hand, increasing the roughness of the non-graphic surface can help to evenly coat the silver slurry, avoid performance problems caused by uneven coating, and improve product quality.
[0023] In the preparation process of the composite slurry, sodium citrate is first used as a reducing agent to reduce silver ions to silver element. Furthermore, the remaining sodium citrate will continue to coat the surface of the generated silver element to form a coating layer. The coating layer can prevent the generated nanosilver from agglomerating and reducing its own performance. In addition, the composite slurry uses nanosilver as the main raw material, and additionally adds spherical silica, nanographene and nanosilicon carbide. By coating the composite slurry on the surface of the non-graphic surface and then sintering it: on the one hand, it can effectively improve the mechanical properties of the material, improve its strength and hardness, and make the ceramic copper-clad substrate have better wear resistance and compression resistance; on the other hand, the composite slurry contains a large number of nanostructures, such as spherical silica and nanographene. The microporous structure of these nanostructures helps to absorb and disperse stress, making the ceramic copper-clad substrate less likely to produce microcracks, and its heat cycle resistance is also greatly improved.
[0024] In summary, the finished product prepared by the present invention has good welding bonding strength, heat dissipation and strength, and will have broad application prospects in the fields of electronic devices, aerospace, etc. It can meet the requirements of AC conduction, heat dissipation and structural strength, and provide reliable technical solutions for related industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0026] Figure 1 It is a welding process diagram of the present invention;
[0027] Figure 2 These are two side views of the silver-plated copper-clad substrate of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Source of raw materials:
[0030] Copper-clad substrate (ceramic sheet, provided by Serontech, with specifications of 138*190.5*0.38mm; copper foil, provided by AURUBIS of Germany, with specifications of 132*184*0.3mm; and then processed by Fulehua through high-temperature sintering process to make copper-clad substrate); chip, provided by Shuyang County Babaijiaoyi E-Commerce Co., Ltd., model GBFDJ; spherical silica, provided by Lingshou County Baiyi Mineral Products Processing Plant, with a particle size of 800 mesh; nano-graphene, provided by Lingshou County Jianshi Mineral Powder Factory, with a particle size of 2000 mesh; nano-silicon carbide, provided by Qinghe County Chaotai Metal Materials Co., Ltd., with a particle size of 600 mesh; corundum, model 400#, the main component of which is Al2O3.
[0031] Example 1: Step 1: Pickling and sandblasting the surface of the copper-clad substrate; wherein the pickling process: immersing the copper-clad substrate in 20% hydrochloric acid with a volume fraction of 20s; sandblasting: first preparing a 25wt% corundum suspension, and then spraying the corundum suspension onto the surface of the copper-clad substrate, maintaining a pressure of 2.5kg / cm, a linear speed of 1.7m / min, and a tank temperature of 25°C. After sandblasting, keep the surface clean and ensure that the water conductivity of the washing water is 1us / cm 3 ;
[0032] One side of the treated copper-clad substrate is used as a graphic surface for selective silver plating; the other side is used as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate; wherein during the selective silver plating and full silver plating, the plating solution includes 1.0 g / L silver ions, 5 g / L copper ion complexing agent, 0.5 g / L bithiazole compounds, 0.5 g / L nitrogen-containing indole compounds, 0.05 g / L benzotriazole, 40 ml / L methane sulfonic acid, and 0.5 g / L polyphenylene tetracarboxamide; the silver plating pH is 1.0, the silver plating temperature is 60°C, the silver plating time is 5 min, and the silver plating thickness is 0.6 um;
[0033] Step 2: The non-patterned surface of the silver-plated copper-clad substrate is sequentially subjected to sandblasting, coated with a composite slurry, and kept at high temperature to remove the organic solvent; wherein the sandblasting treatment: first prepare a 25wt% corundum suspension, and then spray the corundum suspension onto the non-patterned surface of the silver-plated copper-clad substrate, maintaining a pressure of 2.5kg / cm, a linear speed of 1.7m / min, and a tank temperature of 25°C. After sandblasting, the surface is kept clean and the conductivity of the washed water is ensured to be 1us / cm 3 ; High temperature insulation parameter is 120℃ insulation for 4h;
[0034] Preparation process of composite slurry: heat a silver nitrate solution with a concentration of 0.6g / L to boiling, then add a sodium citrate solution with a concentration of 8g / L and stir to react for 2h, cool to 30°C after the reaction, then add a sodium citrate solution with a concentration of 450g / L for flocculation, centrifuge and remove the supernatant after the flocculation to obtain nano silver slurry; mix the nano silver slurry with propanol, and ultrasonically disperse it uniformly to obtain solution 1; mix spherical silica, nano graphene, nano silicon carbide and propanol, and ultrasonically disperse it uniformly to obtain solution 2; mix solution 1 and solution 2 uniformly, then add acetone to mix uniformly, then centrifuge and remove the supernatant to obtain composite slurry; the mass ratio of nano silver slurry and propanol in solution 1 is 1:3; the mass ratio of spherical silica, nano graphene, nano silicon carbide and propanol in solution 2 is 0.6:0.3:0.1:10; the mass content of nano silver in the composite slurry is 96%;
[0035] The Sn96.5Ag3.0Cu0.5 alloy solder sheet was attached to the non-patterned surface of the treated silver-plated copper-clad substrate, sintered and dissolved at 1083°C for 2 hours, and then the chip was placed, and soldered at 300°C for 4 hours to finally prepare a ceramic copper-clad substrate.
[0036] Example 2: Step 1: pickling and sandblasting the surface of the copper-clad substrate; wherein the pickling process: immersing the copper-clad substrate in 15% hydrochloric acid for 17 seconds; sandblasting: first preparing a 20wt% corundum suspension, and then spraying the corundum suspension onto the surface of the copper-clad substrate, maintaining a pressure of 2kg / cm, a linear speed of 1.5m / min, and a tank temperature of 20°C. After sandblasting, keep the surface clean and ensure that the water conductivity of the washing water is <2us / cm 3 ;
[0037] One side of the treated copper-clad substrate is used as a graphic surface for selective silver plating; the other side is used as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate; wherein during the selective silver plating and full silver plating, the plating solution includes 1.0 g / L silver ions, 5 g / L copper ion complexing agent, 0.5 g / L bithiazole compounds, 0.5 g / L nitrogen-containing indole compounds, 0.05 g / L benzotriazole, 40 ml / L methane sulfonic acid, and 0.5 g / L polyphenylene tetracarboxamide; the silver plating pH is 0.7, the silver plating temperature is 55° C., the silver plating time is 3 min, and the silver plating thickness is 0.5 um;
[0038] Step 2: The non-patterned surface of the silver-plated copper-clad substrate is sequentially subjected to sandblasting, coated with a composite slurry, and kept at high temperature to remove the organic solvent; wherein the sandblasting treatment: firstly prepare a 20wt% corundum suspension, and then spray the corundum suspension onto the non-patterned surface of the silver-plated copper-clad substrate, maintain a pressure of 2kg / cm, a linear speed of 1.4m / min, and a tank temperature of 20°C, keep the surface clean after sandblasting, and ensure that the conductivity of the washed water is 1us / cm 3 ; High temperature insulation parameter is 110℃ insulation for 3h;
[0039] Preparation process of composite slurry: heat a silver nitrate solution with a concentration of 0.6g / L to boiling, then add a sodium citrate solution with a concentration of 8g / L and stir to react for 1.5h, cool to 27°C after the reaction, then add a sodium citrate solution with a concentration of 450g / L for flocculation, centrifuge and remove the supernatant after the flocculation to obtain nano silver slurry; mix the nano silver slurry with propanol, and ultrasonically disperse it uniformly to obtain solution 1; mix spherical silica, nano graphene, nano silicon carbide and propanol, and ultrasonically disperse it uniformly to obtain solution 2; mix solution 1 and solution 2 uniformly, then add acetone to mix uniformly, then centrifuge and remove the supernatant to obtain composite slurry; the mass ratio of nano silver slurry and propanol in solution 1 is 1:3; the mass ratio of spherical silica, nano graphene, nano silicon carbide and propanol in solution 2 is 0.6:0.3:0.1:10; the mass content of nano silver in the composite slurry is 96%;
[0040] The Sn96.5Ag3.0Cu0.5 alloy solder sheet was attached to the non-patterned surface of the treated silver-plated copper-clad substrate, sintered and dissolved at 1075°C for 1.6 hours, and then the chip was placed, and soldered at 250°C for 3.5 hours to finally prepare a ceramic copper-clad substrate.
[0041] Example 3: Step 1: Pickling and sandblasting the surface of the copper-clad substrate; wherein the pickling process: immersing the copper-clad substrate in 5% hydrochloric acid for 15 seconds; sandblasting: first preparing a 15wt% corundum suspension, and then spraying the corundum suspension onto the surface of the copper-clad substrate, maintaining a pressure of 1.5kg / cm, a linear speed of 1.3m / min, and a tank temperature of 15°C. After sandblasting, keep the surface clean and ensure that the water conductivity of the washing water is 1us / cm 3 ;
[0042] One side of the treated copper-clad substrate is used as a graphic surface for selective silver plating; the other side is used as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate; wherein during the selective silver plating and full silver plating, the plating solution includes 1.0 g / L silver ions, 5 g / L copper ion complexing agent, 0.5 g / L bithiazole compounds, 0.5 g / L nitrogen-containing indole compounds, 0.05 g / L benzotriazole, 40 ml / L methane sulfonic acid, and 0.5 g / L polyphenylene tetracarboxamide; the silver plating pH is 0.5, the silver plating temperature is 50° C., the silver plating time is 2 min, and the silver plating thickness is 0.3 um;
[0043] Step 2: The non-patterned surface of the silver-plated copper-clad substrate is sequentially subjected to sandblasting, coated with a composite slurry, and kept at high temperature to remove the organic solvent; wherein the sandblasting treatment: first prepare a 15wt% corundum suspension, and then spray the corundum suspension onto the non-patterned surface of the silver-plated copper-clad substrate, maintaining a pressure of 1.5kg / cm, a linear speed of 1.3m / min, and a tank temperature of 15°C. After sandblasting, the surface is kept clean and the conductivity of the washed water is ensured to be 1us / cm 3 ; High temperature insulation parameter is 100℃ insulation for 2h;
[0044] Preparation process of composite slurry: heat a silver nitrate solution with a concentration of 0.6g / L to boiling, then add a sodium citrate solution with a concentration of 8g / L and stir to react for 1h, cool to 25°C after the reaction, then add a sodium citrate solution with a concentration of 450g / L for flocculation, centrifuge and remove the supernatant after the flocculation to obtain nano silver slurry; mix the nano silver slurry with propanol, and ultrasonically disperse it uniformly to obtain solution 1; mix spherical silica, nano graphene, nano silicon carbide and propanol, and ultrasonically disperse it uniformly to obtain solution 2; mix solution 1 and solution 2 uniformly, then add acetone to mix uniformly, then centrifuge and remove the supernatant to obtain composite slurry; the mass ratio of nano silver slurry to propanol in solution 1 is 1:3; the mass ratio of spherical silica, nano graphene, nano silicon carbide and propanol in solution 2 is 0.6:0.3:0.1:10; the mass content of nano silver in the composite slurry is 96%;
[0045] The Sn96.5Ag3.0Cu0.5 alloy solder sheet was attached to the non-patterned surface of the treated silver-plated copper-clad substrate, sintered and dissolved at 1070°C for 1.2 hours, and then the chip was placed and soldered at 200°C for 3 hours to finally prepare a ceramic copper-clad substrate.
[0046] Embodiment 4: The pickling and sandblasting in step 1 are removed, and the steps of coating the composite slurry and removing the organic solvent by high temperature insulation in step 2 are removed. The rest is the same as in embodiment 1, and the specific steps are as follows: Step 1: One side of the copper-clad substrate is used as a graphic surface for selective silver plating; the other side is used as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate; wherein during the selective silver plating and full silver plating, the plating solution includes 1.0g / L silver ions, 5g / L copper ion complexing agent, 0.5g / L bithiazole compounds, 0.5g / L nitrogen-containing indole compounds, 0.05g / L benzotriazole, 40ml / L methanesulfonic acid, and 0.5g / L polyphenylene tetracarboxamide; the silver plating pH is 1.0, the silver plating temperature is 60°C, the silver plating time is 5min, and the silver plating thickness is 0.6um;
[0047] Step 2: sandblast the non-patterned surface of the silver-plated copper-clad substrate; sandblasting process: first prepare a 25wt% corundum suspension, then spray the corundum suspension onto the non-patterned surface of the silver-plated copper-clad substrate, maintain the pressure at 2.5kg / cm, the line speed at 1.7m / min, and the tank temperature at 25°C, keep the surface clean after sandblasting, and ensure that the water conductivity of the washed water is 1us / cm 3 ; High temperature insulation parameter is 120℃ insulation for 4h;
[0048] The Sn96.5Ag3.0Cu0.5 alloy solder sheet was attached to the non-patterned surface of the treated silver-plated copper-clad substrate, sintered and dissolved at 1083°C for 2 hours, and then the chip was placed, and soldered at 300°C for 4 hours to finally prepare a ceramic copper-clad substrate.
[0049] Comparative Example 1: The steps of coating the composite slurry and removing the organic solvent by high temperature insulation in step 2 are removed, and the rest are the same as Example 1, and the specific steps are as follows: Step 1: The surface of the copper-clad substrate is pickled and sandblasted; wherein the pickling process: the copper-clad substrate is immersed in hydrochloric acid with a volume fraction of 20% for 20s; sandblasting: first prepare a corundum suspension with a concentration of 25wt%, and then spray the corundum suspension onto the surface of the copper-clad substrate, maintaining a pressure of 2.5kg / cm, a linear speed of 1.7m / min, and a tank temperature of 25°C. After sandblasting, keep the surface clean and ensure that the water conductivity of the washed water is 1us / cm 3 ;
[0050] One side of the treated copper-clad substrate is used as a graphic surface for selective silver plating; the other side is used as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate; wherein during the selective silver plating and full silver plating, the plating solution includes 1.0 g / L silver ions, 5 g / L copper ion complexing agent, 0.5 g / L bithiazole compounds, 0.5 g / L nitrogen-containing indole compounds, 0.05 g / L benzotriazole, 40 ml / L methane sulfonic acid, and 0.5 g / L polyphenylene tetracarboxamide; the silver plating pH is 1.0, the silver plating temperature is 60°C, the silver plating time is 5 min, and the silver plating thickness is 0.6 um;
[0051] Step 2: sandblast the non-patterned surface of the silver-plated copper-clad substrate; wherein the sandblasting treatment: first prepare a 25wt% corundum suspension, and then spray the corundum suspension onto the non-patterned surface of the silver-plated copper-clad substrate, maintain the pressure at 2.5kg / cm, the line speed at 1.7m / min, and the tank temperature at 25°C, keep the surface clean after sandblasting, and ensure that the water conductivity of the washing water is 1us / cm 3 ;
[0052] The Sn96.5Ag3.0Cu0.5 alloy solder sheet was attached to the non-patterned surface of the treated silver-plated copper-clad substrate, sintered and dissolved at 1083°C for 2 hours, and then the chip was placed, and soldered at 300°C for 4 hours to finally prepare a ceramic copper-clad substrate.
[0053] Comparative Example 2: The sandblasting steps of step 1 and step 2 are removed, and the rest are the same as Example 1, and the specific steps are as follows: Step 1: The surface of the copper-clad substrate is pickled; wherein the pickling process: the copper-clad substrate is immersed in hydrochloric acid with a volume fraction of 20s;
[0054] One side of the treated copper-clad substrate is used as a graphic surface for selective silver plating; the other side is used as a non-graphic surface for full silver plating to obtain a silver-plated copper-clad substrate; wherein during the selective silver plating and full silver plating, the plating solution includes 1.0 g / L silver ions, 5 g / L copper ion complexing agent, 0.5 g / L bithiazole compounds, 0.5 g / L nitrogen-containing indole compounds, 0.05 g / L benzotriazole, 40 ml / L methane sulfonic acid, and 0.5 g / L polyphenylene tetracarboxamide; the silver plating pH is 1.0, the silver plating temperature is 60°C, the silver plating time is 5 min, and the silver plating thickness is 0.6 um;
[0055] Step 2: coating the non-patterned surface of the silver-plated copper-clad substrate with the composite slurry and heat-insulating at high temperature to remove the organic solvent; wherein the high temperature insulation parameter is 120° C. for 4 hours;
[0056] Preparation process of composite slurry: heat a silver nitrate solution with a concentration of 0.6g / L to boiling, then add a sodium citrate solution with a concentration of 8g / L and stir to react for 2h, cool to 30°C after the reaction, then add a sodium citrate solution with a concentration of 450g / L for flocculation, centrifuge and remove the supernatant after the flocculation to obtain nano silver slurry; mix the nano silver slurry with propanol, and ultrasonically disperse it uniformly to obtain solution 1; mix spherical silica, nano graphene, nano silicon carbide and propanol, and ultrasonically disperse it uniformly to obtain solution 2; mix solution 1 and solution 2 uniformly, then add acetone to mix uniformly, then centrifuge and remove the supernatant to obtain composite slurry; the mass ratio of nano silver slurry and propanol in solution 1 is 1:3; the mass ratio of spherical silica, nano graphene, nano silicon carbide and propanol in solution 2 is 0.6:0.3:0.1:10; the mass content of nano silver in the composite slurry is 96%;
[0057] The Sn96.5Ag3.0Cu0.5 alloy solder sheet was attached to the non-patterned surface of the treated silver-plated copper-clad substrate, sintered and dissolved at 1083°C for 2 hours, and then the chip was placed, and soldered at 300°C for 4 hours to finally prepare a ceramic copper-clad substrate.
[0058] Detection test:
[0059] Roughness test: The surface of the ceramic copper-clad substrate has complex undulations, with continuous peaks and valleys of different heights and intervals. The larger undulations are called "flatness" and the smaller undulations are called "surface roughness". Ra is the arithmetic mean roughness, which represents the average value of the absolute value of the roughness on the reference length. Rz describes the fluctuation range or degree of undulation of the surface, and is usually used to evaluate the overall roughness of the surface. This test uses the Japanese Mitutoyo, SJ-410 handheld surface roughness measuring instrument to measure the surface roughness of the product. For each product, 5 sets of data from 4 edges and the middle position are selected, and the average value of the 5 sets of data is calculated as the final result.
[0060] Coating test: This test uses Fisher X-ray for testing. Fisher X-ray mainly uses the penetration principle of X-rays to detect the surface coating of the product of the present invention. When testing the silver-plated surface of copper-clad laminates, X-rays will penetrate the silver-plated layer and be absorbed by the copper-clad laminate. According to the different degrees of absorption of X-rays by materials of different densities and thicknesses, the density, thickness and possible defects of the silver-plated layer can be determined by detecting the transmission and absorption of X-rays, thereby obtaining relevant data. The detection instrument compares these data with the pre-set standards to determine the quality and accuracy of the surface coating to ensure that the coating thickness and uniformity meet the required specifications. Five measuring points are selected for each product in the shape of "Z", and the average value of the data from the five measuring points is taken as the final result.
[0061]
[0062]
[0063] Table 3: Comparison of silver coating test before and after sandblasting
[0064]
[0065] Table 1 is the roughness test record before sandblasting of Example 4, Table 2 is the roughness test record after sandblasting of Example 4, and Table 3 is the comparison of silver plating test before and after sandblasting; the data conclusions are as follows:
[0066] a. Before sandblasting: average value Ra: 0.725um, Rz: 4.225um;
[0067] b. After sandblasting: average value Ra: 0.808um, Rz: 5.813um;
[0068] c. After sandblasting, the surface roughness of the ceramic copper-clad substrate will slightly increase;
[0069] e. Before sandblasting: maximum value of coating 0.57um, minimum value: 0.38um, difference: 0.19um, average value: 0.486um;
[0070] f. After sandblasting: the maximum value of the coating is 0.48um, the minimum value is 0.39um, the difference is 0.09um, and the average value is 0.442um;
[0071] g. After sandblasting, the coating difference is smaller and more uniform.
[0072] Conclusion: The finished copper-clad ceramic substrates prepared in Examples 1 to 3 of the present invention have good welding bonding strength, which can enhance the bonding strength of the welding joints during high-temperature welding and ensure welding quality. By adding the thermal conductivity of materials such as nano-silver, nano-graphene and nano-silicon carbide and the excellent thermal conductivity of metallic silver, the ceramic copper-clad substrate has excellent heat dissipation, which helps to reduce the operating temperature of electronic devices and improve their performance stability. In addition, by adding nano-graphene and nano-silicon carbide, the mechanical strength of the substrate can be enhanced, so that the ceramic copper-clad substrate has good strength and durability.
[0073] Therefore, in Comparative Example 1, the steps of coating the composite slurry and removing the organic solvent by high-temperature insulation in step 2 are removed, and the welding bonding strength and strength of the ceramic copper-clad substrate will be reduced; in Comparative Example 2, the sandblasting steps of steps 1 and 2 are removed, and the welding bonding strength and stability of the ceramic copper-clad substrate will be reduced.
[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0075] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for welding a ceramic copper-clad substrate selectively silver-plated, characterized in that: The following steps are involved: Step 1: Take a copper-clad substrate, use one side of the copper-clad substrate as a pattern surface, and perform selective silver plating; The other side is used as a non-patterned surface and is fully silver-plated to obtain a silver-plated copper-clad substrate; Step 2: attaching the solder sheet to the non-patterned surface of the silver-plated copper-clad substrate, sintering and dissolving at high temperature, placing the chip, and finally preparing the ceramic copper-clad substrate through high-temperature welding; before attaching the solder sheet to the non-patterned surface of the silver-plated copper-clad substrate, sandblasting, coating of composite slurry, and high-temperature insulation are required to remove organic solvents; The preparation process of the composite slurry is as follows: heating a silver nitrate solution with a concentration of 0.6-0.7 g / L to boiling, adding a sodium citrate solution with a concentration of 8-10 g / L and stirring for reaction for 1-2 hours, cooling to 25-30° C. after the reaction, adding a sodium citrate solution with a concentration of 400-500 g / L for flocculation, centrifuging and removing the supernatant after the flocculation to obtain a nano silver slurry; mixing the nano silver slurry with propanol, and uniformly dispersing by ultrasonication to obtain a solution 1; mixing spherical silica and nano silica Graphene, nano-silicon carbide and propanol are mixed and ultrasonically dispersed to obtain solution 2; solution 1 and solution 2 are mixed evenly, acetone is added and mixed evenly, and then centrifuged and supernatant is removed to obtain a composite slurry; the mass ratio of nano-silver slurry to propanol in solution 1 is 1: (3-3.5); the mass ratio of spherical silica, nano-graphene, nano-silicon carbide and propanol in solution 2 is (0.5-0.8): 0.3: 0.1: 10; the mass content of nano-silver in the composite slurry is 96-98%.
2. A method for welding a ceramic copper-clad substrate selectively silver-plated surface according to claim 1, characterized in that: In step 1, when the graphic surface of the copper-clad substrate is selectively silver-plated, the unnecessary area of the graphic surface is masked with ink, the area requiring silver plating is exposed for plating, and the non-graphic surface of the copper-clad substrate is fully silver-plated, and finally a silver-plated copper-clad substrate is obtained; wherein during the selective silver plating and the full silver plating, the plating solution includes 1.0-2.0 g / L silver ions, 5-30 g / L copper ion complexing agent, 0.5-2.0 g / L bithiazole compounds, 0.5-1.5 g / L nitrogen-containing indole compounds, 0.05-0.1 g / L benzotriazole, 40-60 ml / L methane sulfonic acid, and 0.5-1.5 g / L polyphenylene tetracarboxamide; the silver plating pH is 0.5-1.0, the silver plating temperature is 50-60° C., the silver plating time is 2-5 min, and the silver plating thickness is 0.3-0.6 um.
3. A method for welding a ceramic copper-clad substrate selectively silver-plated surface according to claim 1, characterized in that: In step 1, the surface of the copper clad substrate needs to be pickled and sandblasted before silver plating.
4. A method for welding a ceramic copper-clad substrate selectively silver-plated surface according to claim 3, characterized in that: Pickling process: immerse the copper-clad substrate in 2-20% hydrochloric acid by volume for 15-20 seconds; Sandblasting: first prepare a 15-25wt% corundum suspension, then spray the corundum suspension onto the surface of the copper-clad substrate, maintain a pressure of 1.5-2.5kg / cm, a linear speed of 1.3-1.7m / min, and a tank temperature of 15-25℃. Keep the surface clean after sandblasting and ensure that the conductivity of the washing water is less than 2us / cm 3 .
5. A method for welding a ceramic copper-clad substrate selectively silver-plated surface according to claim 1, characterized in that: In step 2, sandblasting: first prepare a 15-25wt% corundum suspension, and then spray the corundum suspension onto the non-patterned surface of the silver-plated copper-clad substrate, maintaining a pressure of 1.5-2.5kg / cm, a linear speed of 1.3-1.7m / min, and a bath temperature of 15-25°C. After sandblasting, keep the surface clean and ensure that the conductivity of the washed water is less than 2us / cm. 3 ; High temperature insulation parameters: 100-120℃ insulation for 2-4h.
6. A method for welding a ceramic copper-clad substrate selectively silver-plated surface according to claim 1, characterized in that: In step 2, the solder sheet is any one of Sn96.5Ag3.0Cu0.5 alloy, Sn95.2Ag4.0Cu0.8 alloy, and Sn97.2Ag2.5Cu0.3 alloy.
7. A welding method for solving the selective silver-plated surface of a ceramic copper-clad substrate according to claim 1, characterized in that: In step 2, high temperature sintering dissolution parameters: sintering temperature is 1065-1083°C, sintering time is 1-2h; High temperature welding parameters: welding temperature is 200-300℃, welding time is 50-80min.
Citation Information
Patent Citations
Copper sheet surface treatment method
CN113799002A
Local silver plating method for copper-clad ceramic substrate
CN114525500A
Ceramic circuit board and semiconductor device combined structure
CN219876270U